Animated Learning Videos Based on Discovery Learning Effectively Teach Fraction Material in Fourth-Grade Elementary School - I Putu Era Satria Wiguna (Universitas Pendidikan Ganesha, 2025)
Low student learning outcomes in Mathematics remain an ongoing issue. This study aims to describe the design process of animated learning video media, assess its quality, and evaluate the effectiveness of Discovery Learning-based animated learning video media on fraction material. The subjects of this study were fourth-grade elementary school students. This research utilized the ADDIE development model, with data collection methods using questionnaires. Data analysis was conducted using descriptive quantitative analysis and inferential statistics techniques. The results of this study are as follows: (1) The design and development of Discovery Learning-based animated learning video media obtained a percentage score of 90.90% (very good). (2) The quality of the animated learning video media, as evaluated by experts, received the following ratings: subject matter experts at 93.33% (very good), instructional design experts at 93.75% (very good), and learning media experts at 93.33% (very good). Student responses in individual trials obtained a percentage of 91.66% (very good), while small group trials scored 93.33% (very good). (3) The effectiveness of the animated learning video media was tested using a correlated t-test, yielding a t-calculated value greater than t-table (-13.60 > 1.699). Based on these calculations, it can be concluded that Discovery Learning-based animated learning video media is effective for teaching fraction material in fourth-grade elementary school Mathematics.